Grote verzamelingen (de); verzameling Tony Herbert. (Brussel : éditions de la Connaissance S.A., 1957)
Anthoons, Willy ; van den Berghe, Frits ; Bertrand, Gaston ; Bonnet, Anne ; Brusselmans, Jean ; Burssens, Jan ; Caille, Pierre ; Daeye, Hippolyte ; Grard, Georges ; Jespers, Oscar ; Leplae, Charles ; Van Lint, Louis ; Mendelson, Marc ; Mortier, Antoine ; Permeke, Constant ; Puvrez, Henri ; De Smet, Gust ; Tytgat, Edgard ; Willequet, André ; de Woestyne, Gustave Van ; Wouters, Rik
boek